Not all plant-based diets are associated with benefits on mortality: the Moli-sani Study: Marialaura Bonaccio. (25th October 2022) - Bonaccio, M; Di Castelnuovo, A; Costanzo, S; Ruggiero, E; Esposito, S; Persichillo, M; Cerletti, C; Donati, MB; de Gaetano, G; Iacoviello, L
Abstract: Background: Vegetarians diets are characterized by the absence of some animal foods (e.g. red and processed meats), and a high consumption of plant-based foods. However, plant-based foods can include foods with varying nutritional value and health effects. We examined the association of three different pro-vegetarian (PVG) food patterns defined as general (gPVG), healthful (hPVG) and unhealthful (uPVG), with the risk of all-cause and cardiovascular disease (CVD) mortality in Italians. Methods: Longitudinal analysis on 22, 912 men and women (mean age 55±12 y) from the Moli-sani Study (2005-2010) followed up for 11.2 y (median). Food intake was assessed by a 188-item FFQ. A provegetarian food pattern (FP) was constructed by assigning positive scores to plant foods and reverse scores to animal foods. A healthful and an unhealthful pro-vegetarian FP, which distinguished between healthy (e.g. fruits, vegetables, legumes) and less-healthy plant foods (e.g. fruit juices, potatoes, sugary beverages), were also built up. Results: In multivariable-adjusted analyses controlled for known risk factors, higher adherence to a gPVG was associated with lower all-cause (HR = 0.83; 95%CI 0.73-0.94) but not CVD mortality (HR = 0.90; 0.72-1.12). Increasing adherence to a hPVG was associated with reduced all-cause mortality risk (HR = 0.82; 0.72-0.95) as well as lower risk of CVD mortality (HR = 0.75; 0.59-0.95). Finally, the uPVG was directly associated with both all-cause (HR = 1.17; 1.03-1.33) and CVD mortality risks (HR = 1.23; 0.99-1.53). Conclusions: A general pro-vegetarian food pattern was associated with longer survival in Italians. Preferring healthful vegetarian foods provided protection against CVD mortality too. Consistently, a large dietary share of unhealthful vegetarian foods, mostly highly processed, was associated with increased risk mortality. Thus the quality of the plant food consumed is paramount to achieve diet-related benefits on mortality. Key messages:  A pro-vegetarian food pattern was associated with longer survival but preferring healthful vegetarian foods provided protection against CVD mortality too.  The quality of the plant food consumed is paramount to achieve diet-related benefits on mortality.